Insights into the Reflection of Oman Vision 2040’s Priorities and Strategic Directives in the Newly Introduced ELT Textbook Series “Team Together Oman”: Content Analysis and Teachers’ Perspectives - Al-Siyabi, Salama Saif Hamed; Al-Harthi, Khadija Mohammed Nasser (Journal of Curriculum and Teaching Methodology, 2025)
This study aimed to examine the alignment of the newly introduced English language teaching syllabus, Team Together Oman, with the priorities and strategic directives outlined in Oman Vision 2040. It also aimed to explore English language teachers' perspectives on this alignment, highlighting both the syllabus's advantages and the challenges educators face in achieving coherence with Oman Vision 2040’s objectives.A descriptive research design was employed, incorporating content analysis to evaluate the Graded Readers used in the Team Together Oman textbook series. Two reviewers have analysed the content of the syllabus. Additionally, a questionnaire was utilized to gather data on teachers’ perceptions of the newly introduced textbooks. The findings indicate that Team Together Oman strongly reflects the goals of Oman Vision 2040 explicitly and implicitly. Regarding the questionnaire findings, participant teachers agree that Graded Readers effectively enhance students' reading skills (M=4.01), and they appreciate how the vocabulary used in the stories aligns with the vocabulary taught in the units, as seen in the high mean score (M=4.41). However, there are concerns regarding time constraints, with a relatively high standard deviation (1.68) indicating varied opinions about whether there is sufficient classroom time to teach the readings. Notably, teachers express strong agreement about the need for training programs to better align teaching practices with Oman Vision 2040, scoring the highest mean with the lowest standard deviation (M=4.51), reflecting a clear desire for professional development and support. It is recommended that further studies be conducted to investigate the alignment between the priorities and strategic directives of Oman Vision 2040 and the content of Team Together Oman textbooks across other grade levels.
Keywords: Oman Vision 2040; Team Together Oman series; Syllabus; Curriculum; Graded Readers; ELT; EFL